A Fractional Order Hepatitis C Mathematical Model with Mittag-Leffler Kernel. (26th October 2021) - Alshehri, Hashim M.; Khan, Aziz
Abstract : In this paper, a mathematical fractional order Hepatitis C virus (HCV) spread model is presented for an analytical and numerical study. The model is a fractional order extension of the classical model. The paper includes the existence, singularity, Hyers-Ulam stability, and numerical solutions. Our numerical results are based on the Lagrange polynomial interpolation. We observe that the model of fractional order has the same behavior of the solutions as the integer order existing model.